2018
DOI: 10.1007/s10940-018-9377-x
|View full text |Cite
|
Sign up to set email alerts
|

Crime and Inflation in U. S. Cities

Abstract: Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Certain types of crimes and social classes are inversely connected for the most part, and the most dangerous types of crimes do tend to happen in lower-class neighborhoods and communities (Anderson et al, 2013;MacDonald et al, 2012;Rosenfeld et al, 2018). This is not to say that crime does not occur in rich areas, but differences can be seen in the types of crimes often committed across class boundaries (e.g., gang violence, white-collar crime; Browning et al, 2017;Kelly et al, 2010;Moore & Recker, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain types of crimes and social classes are inversely connected for the most part, and the most dangerous types of crimes do tend to happen in lower-class neighborhoods and communities (Anderson et al, 2013;MacDonald et al, 2012;Rosenfeld et al, 2018). This is not to say that crime does not occur in rich areas, but differences can be seen in the types of crimes often committed across class boundaries (e.g., gang violence, white-collar crime; Browning et al, 2017;Kelly et al, 2010;Moore & Recker, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals are at increased risk of being victimized due to their positions in the social structure, their lifestyles, their social status, their living situations, etc. (Burchfield & Silver, 2013;Kelly et al, 2010;Ridgeway & MacDonald, 2016;Rosenfeld, Vogel, & McCuddy, 2018 …”
Section: Literature Reviewmentioning
confidence: 99%
“…Matt Vogel, Tim McCuddy, and I wondered whether the national‐level results would hold at the city level. We looked at the effect of inflation on the change in acquisitive crime rates in 17 U.S. cities for which the inflation data were available between 1960 and 2013 (Rosenfeld, Vogel, and McCuddy, ). We found that, on average, rising inflation rates boosted and falling inflation rates lowered acquisitive crime rates in the 17‐city sample.…”
Section: Crime Trends and The Economymentioning
confidence: 99%
“…Another consequence of male criminality is that there are increasing levels of fatherless children throughout racial groups, as these men are viewed as reproductive partners, but not as traditional husbands or fathers. (Rosenfeld et al 2018) This situation further erodes the family institution when coupled with the wage inflation that has been more prominent for females in the US, which leads many women (even those with low labor productivity) to eschew husbands as providers in exchange for provision from the state, their own wages, or older family members. (Schneider et al 2018) The presence of increasing prices has also been shown to impact the fertility rates of married couples over time and in different cultural and economic settings.…”
Section: Introductionmentioning
confidence: 99%